A unique Fe-rich carbonate chimney associated with cold seeps in the Northern Okinawa Trough, East China Sea. (January 2015) - Sun, Zhilei; Wei, Helong; Zhang, Xunhua; Shang, Luning; Yin, Xijie; Sun, Yunbao; Xu, Lei; Huang, Wei; Zhang, Xianrong
Abstract: The East China Sea is an important marginal sea of the Western Pacific Ocean, from which natural gas hydrate sample has not been acquired so far. Recently, copious carbonate chimneys have been discovered in turbidite deposits in the olistostrome zone located on the west slope of the northern section of Okinawa Trough. Here, the petrology, geochemistry and chronology of an iron-rich carbonate chimney were characterized, confirming a close relationship between its formation and the dissociation of natural gas hydrate beneath the chimney in OT. A distinctive relationship has been observed between goethite and total carbonate contents along with a negative correlation between Fe and Ca contents. Conversely, abundant Fe accumulated on carbonate substrate by mineralized microorganisms. The δ 13 C values of the chimney wall were from −27.56 to −43.66‰ (average: −37.18‰, V-PDB), implying anaerobic oxidation of methane (AOM) as a predominant controlling factor on carbonate precipitation. As no pyrite and organic residues were identified in the iron-rich chimney, it was assumed that AOM was coupled to the iron reduction reaction at least to some extent during the chimney growth owing to the local deficiency of sulfate supply. The δ 56 Fe values of bulk chimney wall (ranging from −0.316‰ to −0.023‰, average −0.134‰) suggest mass and isotope exchanges between the chimney and ambient environment during its growth history, whereas the enrichment of δ 18 O of the carbonate implies these carbonate sourcing from hydrate dissociation underlying our sampling site. This assumption has been supported by a distinct bottom simulation reflector (BSR) and a well-developed fault system beneath the sampling site. This is the first report of cold seepage inside the OT and the identified iron-dependent AOM has shed a new light to the Carbon cycle related to the marine methane oxidation, particularly before the Great Oxidation Event ~2.45 Ga ago. Highlights: Fe-rich cold seep carbonate chimney is related to the dissociation of gas hydrate in Okinawa Trough. AOM was coupled to the iron reduction reaction during the chimney growth in turbidite deposits. Fe (oxyhydr)oxides was sourced from early diagentic weathering of dark minerals in marine sediments.